Defining Breadth of Hepatitis C Virus Neutralization - Kinchen, Valerie J.; Bailey, Justin R. (Frontiers in Immunology, 2018)
Extraordinary genetic diversity is a hallmark of hepatitis C virus (HCV). Therefore, accurate measurement of the breadth of antibody neutralizing activity across diverse HCV isolates is key to defining correlates of immune protection against the virus, and essential to guide vaccine development. Panels of HCV pseudoparticles (HCVpp) or replication competent cell culture viruses (HCVcc) can be used to measure neutralizing breadth of antibodies. These in vitro assays have been used to define neutralizing breadth of antibodies in serum, to characterize broadly neutralizing monoclonal antibodies, and to identify mechanisms of HCV resistance to antibody neutralization. Recently, larger and more diverse panels of both HCVpp and HCVcc have been described that better represent the diversity of circulating HCV strains, but further work is needed to expand and standardize these neutralization panels.